Influência da urbanização sobre a distribuição e estratégias de defesa de tocas de Athene cunicularia (Molina, 1782) (Aves: Strigiformes) - Franco, Felipe Fina (2017)
The urbanization process causes drastic changes in habitat and species behavior. In birds, these changes influenced the extinction of some species. However, some of these birds, such as Athene cunicularia, have achieved some success in their adaptive process and maintain their populations in anthropic environments, due, mainly, to the success of some defense strategies. The main objective of this study was to measure distribution and abundance of A. cunicularia in urban areas of Uberlândia city. The specific objectives were: i) quantify and compare ocorrency and abundance of this species among urban biotopes, ii) determine frequency and distribution of satellite burrows, by urban biotopes, iii) evaluate the importance of satellite burrows as a defense mechanism of the species and iv) compare depth of burrows in different biotopes. Field activities were carried out from August 2015 to November 2016. Sixty areas were sampled in the different urban areas of the city (North, South, East, West and Center). The number of individuals and burrows in areas classified by urban biotopes was counted, as well as the number of burrows and individuals, and the depth of some burrows for the study of defense behavior were measured. The species was present in 29 of the 60 areas investigated, registering 112 individuals, including 88 adults (male and female), 14 young and 10 pups. In each study area, 96 burrows were recorded, with a mean of 3.14 burrows / areas, of which 22 were refuges, 7 nests and 67 satellite burrows. Residential and Urban Green bio-topes had higher number of individuals and burrows, with a significant difference in relation to the Commercial/Industrial biotope. A greater number of individuals were found in areas with a high number of burrows, showing a positive linear relationship between these variables. The burrow depth was higher, on average, in the urban green area biotopes. We conclude that the species has a wide distribution in the city; However, with a significantly higher num-ber in the Residencial biotope. This same tendency is verified for the distribution of burrows. In areas with a greater number of individuals, the same was observed for the number of satellite burrows. The greater depth of burrows in the urban Green Areas is perhaps due to the greater flow of people, one of the main features of this biotope and one of the greatest threats to A. cunicularia.